Upaya Meningkatkan Keterampilan Membaca Cepat dengan Menggunakan Metode P2R dan Question pada Siswa SMA Negeri 1 Leces Kabupaten Probolinggo - Rini Pujiastutik (Universitas Pendidikan Mandalika, 2021)
This study aims to improve speed reading skills by using the P2R method and questions with a horizontal pattern in class X MIPA 4 SMA Negeri 1 Leces. This research method uses classroom action research. This research data collection technique using tests, observation, interviews and documentation. Meanwhile, the data analysis technique used qualitative and quantitative analysis. The results of this study indicate an increase in the process of learning to read quickly to find the main idea of paragraphs using the P2R method and questions with a horizontal pattern. The results of the increase in speed reading skills from pre-cycle to cycle I reached an average of 52.88% or 185 kpm, an increase of 4% so that it became 56.88% or 199 kpm. Meanwhile, cycle II also increased by 21.9% from an average of 52.88% to 74.78% or 261 kpm. This shows that the increase in speed reading skills from pre-cycle, cycle I, and cycle II has increased good results.